PENGARUH SOLVABILITAS PADA RETURN SAHAM SEBELUM DAN SESUDAH DEPRESIASI NILAI RUPIAH (STUDI EMPIRIS: PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI) - Lisdiyani, Ni Nengah; Widanaputra, Anak Agung Gede Putu (E-Jurnal Akuntansi, 2015)
This study aims to determine the effect of solvabiltas on stock returns before and after the depreciation of the rupiah, and to determine differences in stock returns before and after the depreciation of the rupiah. This research was conducted at the companies listed on the Stock Exchange the period 2013 - 2014 samples were taken by purposive sampling method as many as 78 companies nanufaktur. Techniques used simple regression analysis and two different test average of paired samples. The research proves that solvency has no effect on stock returns before depreciation of the rupiah, and solvency negative effect on stock returns after the depreciation of the rupiah, and there are differences in stock returns before and after the depreciation of the rupiah.
Keywords: Solvency, Dollar Depreciation Value and Stock Return